Understanding the mechanisms of halotolerance in members of Pontixanthobacter and Allopontixanthobacter by comparative genome analysis - Zhou, Peng; Bu, Yu-Xin; Xu, Lin; Xu, Xue-Wei; Shen, Hong-Bin (Frontiers in Microbiology, 2023)
Halotolerant microorganisms have developed versatile mechanisms for coping with saline stress. With the increasing number of isolated halotolerant strains and their genomes being sequenced, comparative genome analysis would help understand the mechanisms of salt tolerance. Six type strains of Pontixanthobacter and Allopontixanthobacter, two phylogenetically close genera, were isolated from diverse salty environments and showed different NaCl tolerances, from 3% to 10% (w/v). Based on the co-occurrence greater than 0.97 between halotolerance and open reading frame (ORF) among the six strains, possible explanations for halotolerance were discussed regarding osmolyte, membrane permeability, transportation, intracellular signaling, polysaccharide biosynthesis, and SOS response, which provided hypotheses for further investigations. The strategy of analyzing genome-wide co-occurrence between genetic diversity and physiological characteristics sheds light on how microorganisms adapt to the environment.